Electrochemical treatment of concentrate from reverse osmosis of sanitary landfill leachate. (1st October 2016) - Labiadh, Lazhar; Fernandes, Annabel; Ciríaco, Lurdes; Pacheco, Maria José; Gadri, Abdellatif; Ammar, Salah; Lopes, Ana
Abstract: Conventional sanitary landfill leachate treatment has recently been complemented and, in some cases, completely replaced by reverse osmosis technology. Despite the good quality of treated water, the efficiency of the process is low and a large volume of reverse osmosis concentrate has to be either discharged or further treated. In this study, the use of anodic oxidation combined with electro-Fenton processes to treat the concentrate obtained in the reverse osmosis of sanitary landfill leachate was evaluated. The anodic oxidation pretreatment was performed in a pilot plant using an electrochemical cell with boron-doped diamond electrodes. In the electro-Fenton experiments, a boron-doped diamond anode and carbon-felt cathode were used, and the influence of the initial pH and iron concentration were studied. For the experimental conditions, the electro-Fenton assays performed at an initial pH of 3 had higher organic load removal levels, whereas the best nitrogen removal was attained when the electrochemical process was performed at the natural pH of 8.8. The increase in the iron concentration had an adverse impact on treatment under natural pH conditions, but it enhanced the nitrogen removal in the electro-Fenton assays performed at an initial pH of 3. The combined anodic oxidation and electro-Fenton process is useful for treating the reverse osmosis concentrate because it is effective at removing the organic load and nitrogen-containing species. Additionally, this process potentiates the increase in the biodegradability index of the treated effluent. Graphical abstract: Highlights: Anodic oxidation + electro-Fenton can be used to treat reverse osmosis concentrate. In the electro-Fenton process, ammonium removal increases with the initial pH. Acidic pH conditions favor COD removal in the electro-Fenton process. For nitrogen removal, anodic oxidation is more effective than electro-Fenton.